Assessing the scope for genetic rescue of an endangered butterfly: the case of the Eltham copper. Issue 5 (11th May 2017) - Roitman, Maria; Gardner, Michael G.; New, Timothy R.; Nguyen, Thuy T. T.; Roycroft, Emily J.; Sunnucks, Paul; Yen, Alan L.; Harrisson, Katherine A.
Abstract: Genetic rescue is an under‐utilised conservation strategy used to boost the genetic diversity and/or fitness of small, isolated populations through the introduction of novel genes. Effective implementation of genetic rescue requires an understanding of the evolutionary history and genetic distinctiveness of populations. The Eltham copper butterfly (ECB) is an endangered subspecies that exists as small, isolated populations across four disjunct regions in Victoria, Australia. Mitochondrial and nuclear sequence data were used to assess the genetic distinctiveness of ECB from its nearest relative: the fiery dull copper butterfly (FDC), explore the evolutionary history and population structure of ECB across its contemporary distribution, and assess the scope for genetic rescue of the most‐threatened ECB population in Eltham‐Greensborough. Findings support the current status of ECB and FDC as distinct evolutionary units, which should continue to be managed separately given current knowledge. Modest population genetic structure across the range of ECB was detected. However, low levels of historical gene flow and shared haplotypes between Eltham‐Greensborough and the northern regions suggest relatively recent divergence. Given relatively recent divergence, low population numbers and low genetic diversity, the population located in the Eltham‐Greensborough region is a strong candidate for genetic rescue. Using established criteria, explicit recommendations are made for the implementation of genetic rescue via translocations. Genetic rescue, together with ongoing habitat management, should improve genetic diversity, fitness and persistence of the ECB in the region most threatened by urban disturbance. Any risks associated with genetic rescue in conservation should be weighed against extinction risk as a result of inaction.